Selection of Mycoprotein-producing yeast as a new source of non-meat proteins - N. Viveros-Lizondo; B. García-Béjar; A. Haro; A. Soriano; M. Arévalo-Villena (Applied Food Research)
A growing trend in the population to prioritize health, the environment and animal welfare has been observed, leading to reduce the consumption of processed foods and meat. This sift has driven research into alternative proteins from plants, insects and microorganisms, with single cell proteins standing out as a promising option. A selection of 835 yeasts was proposed as potential source of protein for reducing the meat content. Firstly, a literature search was carried out to identify those with the highest protein content and best characteristics. As a second screening stage, outgrowth kinetics were analysed to guarantee their efficiency and efficacy during the process. It was stablished a limit of λ 〈 6 h and OD max 〉 1. These criteria were exceeded by 37 % of the total number of strains evaluated. To quantify protein content, the Bradford method was used, and samples were pre-treated with ultrasound (50W/10 min), which significantly increased protein release. A total of 99 strains exceeded the established limit of 50 mg protein/g of dry biomass, of which 39 belonged to the Saccharomyces genus and 60 to non-Saccharomyces genera. The last screening test was the evaluation of yeast growth inhibition after ultrasound treatment. As a result, 53 yeasts were found to meet all the established criteria, representing 16.6 % of the total number. These selected strains are considered promising candidates for use as ingredients in the formulation of meat products with a lower meat content, thus contributing to meet consumer demand for healthier and more sustainable alternatives.